The Effect of Career Development on Employee Performance at Aswin Hotel and Spa Makassar - Firman, Ahmad (JURNAL MANAJEMEN BISNIS, 2021)
This study aims to determine the effect of career development toward employee performance at Aswin Hotels and Spa Makassar. The model used in this study is a questionnaire using a Likert scale. And the method of determining the sample used is a saturated sample with the total sample represented the total population of 53 people. The analytical method used is a simple regression analysis method. The results of this study indicate that career development had a positive and significant effect toward employee performance at the Aswin Hotel and Spa Makassar. Career development affected the performance of Aswin Hotel and Spa Makassar employees by 54.4%, while 45.6% of employee performance variables were affected by other variables who did not observe by researchers.